MEASUREMENT OF QUALITY MANAGEMENT SYSTEM PERFORMANCE IN MEAT PROCESSING - Elena S. Voloshina; Nina I. Dunchenko (Теория и практика переработки мяса, 2017)
Modern methods aimed to ensure the quality of foods require to implement and certify quality management systems in processing plants. In this case, to measure the effectiveness of existing QMS is often a very difficult task for the leadership due to the fragmentation of the measured metrics, or even lack thereof. This points to the relevance of the conducted research.The criteria for effectiveness assessment of the production process of meat processing plants with the use of scaling methods and Shewhart control charts are presented in the article. The authors developed and presented the formulae for the calculation of single indicators used for the further comprehensive assessment. The algorithm of statistical evaluation of the process controllability, which allows in an accessible form to estimate the statistical control of production processes and to organize statistical quality control in the development of quality management systems, is presented The proposed procedure is based on a process approach, the essence of which is the application of the Deming cycle: “Plan — Do — Check — Act”, which makes it easy to integrate it into any existing quality management system.